2017
DOI: 10.1097/igc.0000000000000903
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surgery in the Management of Hydatidiform Mole in Elderly Patients

Abstract: Primary hysterectomy after 40 years old in women affected by HM does not reduce the incidence of GTN and amount of chemotherapy. Although further studies are needed to confirm these results, a careful hCG monitoring should be recommended in these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 10 publications
1
17
0
1
Order By: Relevance
“…In comparison, our study consisted of 37 patients in the prophylactic hysterectomy group, which theoretically should lead to more reliable results. It is worth mentioning that a recent study [ 17 ] showed that hysterectomy after 40 years old in women with HM does not reduce the incidence of GTN. In this study, a total of 76 patients with HM who were over 40 years old were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, our study consisted of 37 patients in the prophylactic hysterectomy group, which theoretically should lead to more reliable results. It is worth mentioning that a recent study [ 17 ] showed that hysterectomy after 40 years old in women with HM does not reduce the incidence of GTN. In this study, a total of 76 patients with HM who were over 40 years old were included.…”
Section: Discussionmentioning
confidence: 99%
“…The prophylactic effect of total hysterectomy is similarly controversial. While some studies demonstrated that it could potentially prevent the malignancy of CHM [ 15 , 16 , 14 ], others argued it could not reduce the incidence of GTN [ 17 , 18 ]. Moreover, few of the above-mentioned studies specifically targeted patients who are at least 40 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Although variables such as maternal age over 40 years and a longer interval to achieve an undetectable β-hCG level are associated with an increased risk of GTN, the benefits of prophylactic chemotherapy and hysterectomy are controversial. [ 16 , 17 ] In contrast to Knol's point of view, [ 8 ] we believe that hysterectomy is not a necessary treatment for patients over 40 years of age (patients 5, 10, 15, and 16), as it showed no obvious benefits in patients with pulmonary deportation. The results of our study favored reducing the use of unnecessary toxic therapies or invasive manipulation after balancing the future risk of GTN with patient safety.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Zhao et al found that the incidence of post-molar GTN in women aged >40 years was significantly lower in patients who had hysterectomy compared to patients who had dilatation and curettage (11% vs 37%, P =0.004) for complete mole [ 24 ]. In contrast, Giorgione et al reported that in women with hydatidiform mole aged >40 years, primary hysterectomy does not reduce the incidence of port-molar GTN when compared with dilatation and curettage (58% vs 30% respectively, P =0.094) [ 25 ]. Moreover, they also found that hysterectomy does not reduce the amount of chemotherapy required to treat GTN, although 42% (5 out of 12) of their patients who had primary hysterectomy achieved complete remission after surgery.…”
Section: Surgery For Hydatidiform Molementioning
confidence: 99%